Pathogenetic aspects and modern possibilities of therapy of vulvovaginal candidiasis - Margarita R. Rakhmatulina; Elena V. Lipova; Viktoria A. Nyanenko (Vestnik Dermatologii i Venerologii)
The literature review presents modern aspects of the etiology and pathogenesis of vulvovaginal candidiasis, highlights issues of immunological resistance and the significance of polymorphic and pathological gene loci, the functioning of which leads to insufficient activation of the immune system in the disease. The mechanisms of formation of biofilms by fungi of the genus Candida on mucous membranes and the role of lactobacillary microflora in preventing their spread, as well as ideas about the prerequisites for the development of vulvovaginal candidiasis are considered. The modern possibilities of drug therapy for vulvovaginal candidiasis, presented in domestic and foreign clinical recommendations, are discussed. The advantages of prescribing fenticonazole, which is active against various types of fungi of the genus Candida, as well as a wide range of anaerobes and microorganisms associated with bacterial vaginosis, are considered, and the results of studies on the effectiveness of the drug are analyzed.